Predictive Value of Two-Dimensional Speckle-Tracking Echocardiography in Patients Undergoing Surgical Ventricular Restoration - Nemchyna, Olena; Solowjowa, Natalia; Dandel, Michael; Hrytsyna, Yuriy; Stein, Julia; Knierim, Jan; Schoenrath, Felix; Hennig, Felix; Falk, Volkmar; Knosalla, Christoph (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Parameters of left ventricular (LV) mechanics, obtained from speckle-tracking echocardiography (STE), were found to be of prognostic value in patients with heart failure and those who underwent cardiac surgery. This study aimed to assess the value of STE in patients scheduled to undergo surgical ventricular restoration (SVR). Methods: One hundred and fifty-eight consecutive patients with baseline STE who underwent SVR due to an LV antero-apical aneurysm were included in the analysis. Preoperative longitudinal STE parameters were evaluated for their association with an outcome, defined as all-cause mortality, LV assist device implantation, or heart transplantation. Echocardiographic follow-up to assess the change in the regional function of the segments remote from the aneurysm was performed in 43 patients at a median of 10 months (IQR: 6 12.7 months) after SVR. Results: During a median follow-up of 5.1 years (IQR: 1.6 8.7 years), events occurred in 68 patients (48 %). Less impaired mean basal end-systolic longitudinal strain (BLS) with a cut-off value ≤ 10.1 % demonstrated strong association with event-free survival, also in patients with an LV shape corresponding to an intermediate shape between aneurysmal and globally akinetic. Initially hypo- or akinetic basal segments with preoperative end-systolic strain ≤ 7.8 % showed a greater improvement in wall motion at the short-term follow-up. Conclusion: Patients with less impaired preoperative BLS exhibited a better event-free survival after SVR, also those with severe LV remodeling. Preserved preoperative segmental longitudinal strain was associated with a greater improvement in regional wall motion after SVR. BLS assessment may play a predictive role in patients with an LV antero-apical aneurysm who are scheduled to undergo SVR.